Face mask use in the community and cutaneous reactions to them during the COVID-19 pandemic: results of a national survey in Italy (Dermatology Reports, 2022)
To mitigate the outbreak of coronavirus disease 2019 pandemic, many countries have imposed the public use of face masks. We investigated attitudes and skin reactions in the Italian individuals wearing face masks during the pandemic. A cross-sectional survey on a random sample (N=1001) of the Italian adult population was conducted in May 2020 by the Italian Group for Epidemiological Research in Dermatology, and the Gallup International Association. Univariable and multivariable regression analysis were used to estimate the odds ratios and their 95% confidence intervals. Most individuals (72.5%) wore a mask, 56.5% used a surgical mask and 53.0% a disposable mask. One-third changed the mask at least once a day, two-thirds kept a distance of at least one meter from each other, 50% washed their hands before wearing a mask, and 17.6% adopted multiple hygienic behaviors. Twenty percent of individuals reported redness, swelling, itching or erosions in the skin area of mask contact; the risk of this reaction was associated with young age, the use of respirators and a history of pre-existing contact eczema, psoriasis or atopic dermatitis. Health educational programs may improve compliance with combined preventive measures and reduce skin reactions.